Pengaruh Pemberian Jus Umbi Bit terhadap Kadar Hemoglobin Ibu Hamil Trimester III - Willya Rizky Fadillah; Retno Widowati; Febry Mutiariami Dahlan (Universitas Baiturrahim, 2023)
WHO data (2020), it estimated that worldwide around 32 million pregnant women have anemia. In Indonesia, the incidence of anemia in pregnant women increased in 2018 by 48.8% when compared to 2013, which was 37.1%. Garut Regency in 2019 the prevalence of pregnant women with anemia was 6669 people. Karangpawitan Health Center in 2021, out of 834 pregnant women, 31.5% experienced anemia in the first trimester and as many as 168 pregnant women in third trimester (20.1%). Non-pharmacologically the treatment and prevention of anemia is by consuming green vegetables, nuts, chicken liver, beet tubers, red guava fruit and others. The content of beet tubers in the list of food ingredients includes 108 mg of folic acid, 27.0 mg of calcium, 43.0 mg of phosphorus, 43 mg of vitamin C, 23 mg of magnesium, 9.6 mg of carbohydrates, 1.0 mg of iron (Ministry of Health RI, 2016). Folic acid is very good to help the formation of the baby's brain and overcome the problem of anemia. The purpose of the study was to determine the effect of beetroot juice on hemoglobin levels of pregnant women in the third trimester at Karangpawitan Public Health Center, Garut Regency. The methodology of this research uses Pre test - Post test with control group design. The population in the study were all pregnant women in the third trimester as many as 129 people The samples in this study were TM III pregnant women who experienced mild anemia using purposive sampling as many as 30 people who were divided into 2 groups, namely 15 people in the experimental group and 15 people in the control group. The instruments used are observation sheets and technical instructions for beetroot juice. Data analysis used Paired T-test and Independent Samples Test. The results of the study the average hemoglobin level in the experimental group before being given beet juice was 9.160 and after beet juice was 10.807, while in the control group before the intervention was 8.933 and after the intervention was 9.813. The bivariate results showed a p-value of 0.000 <0.05. The conclusion is that there is an effect of giving beetroot juice + Fe tablets on hemoglobin levels of pregnant women in the third trimester at Karangpawitan Health Center, Garut Regency In 2023. With this study, consumption of beet root juice can be an alternative in increasing hemoglobin levels in pregnant women.